Pengaruh Aplikasi Pupuk Mikro Zinc (Zn) dan Copper (Cu) terhadap Pertumbuhan dan Produktivitas Tanaman Tomat (Solanum lycopersicum L.) - Sutan Tarmizi Lubis; Eka Tarwaca Susila Putra; Lisa Kawispa Ananda; Azhari Muklis (Universitas Gadjah Mada, 2026)
This study aimed to evaluate the effect of a Zn–Cu compound micronutrient fertilizer on growth, yield components, productivity, and nutrient use efficiency of Servo tomato. The field experiment was conducted in Srigading Village, Sanden Subdistrict, Bantul Regency, Yogyakarta, Indonesia, from January to April 2025. Treatments were arranged in a single-factor Randomized Complete Block Design (RCBD) with eight fertilization levels and four replications, combining NPK fertilizer with graded doses of Zn+Cu micronutrient fertilizer. Soil nutrient analyses were conducted before and after planting, while leaf tissue nutrient analysis was performed prior to harvest. Observed parameters included vegetative growth, yield components, Relative Agronomic Effectiveness (RAE), and fertilizer-use efficiency. The results showed that the combination of micronutrient fertilizer and NPK significantly enhanced nutrient uptake and yield. The highest Cu uptake was obtained in treatment P7 (¾ NPK dose + 1.5 micronutrient dose) at 0.08137 g ha-1, while the highest Zn uptake was recorded in P4 (1 NPK dose + 1 micronutrient dose) at 0.24696 g ha-1. Treatment P7 increased branch number up to three branches per plant and produced the highest yield of 39.50 t ha-1. The RAE value exceeded 100%, indicating that the tested fertilizer was 209.38% as effective as the standard fertilization. These findings highlight that the synergy and balance between macro- and micronutrients play a more critical role in determining productivity than the high uptake of a single nutrient alone.